Aus Fehlern lernen? Was kann man bei der Vergabe des Titels immaterielles Kulturerbe aus den Erfahrungen mit dem materiellen Kulturerbe ableiten und verbessern? - Seng, Eva- Maria (Altes Zeug: Beiträge zur Diskussion zum nachhaltigen Kulturgutschutz)

Literaturwissenschaft - Eke, Norbert Otto; Allkemper, Alo

Das Politische und die Politik im Vormärz

How to Complete Customer Requirements: Using Concept Expansion for Requirement Refinement - Geierhos, Michaela; Bäumer, Frederik Simon (Proceedings of the 21st International Conference on Applications of Natural Language to Information Systems (NLDB))
One purpose of requirement refinement is that higher-level requirements have to be translated to something usable by developers. Since customer requirements are often written in natural language by end users, they lack precision, completeness and consistency. Although user stories are often used in the requirement elicitation process in order to describe the possibilities how to interact with the software, there is always something unspoken. Here, we present techniques how to automatically refine vague software descriptions. Thus, we can bridge the gap by first revising natural language utterances from higher-level to more detailed customer requirements, before functionality matters. We therefore focus on the resolution of semantically incomplete user-generated sentences (i.e. non-instantiated arguments of predicates) and provide ontology-based gap-filling suggestions how to complete unverbalized information in the user’s demand.
Keywords: Requirement refinement; Concept expansion; Ontology-based instantiation of predicate-argument structure

‚Reden‘ über Dichtung. Poetik-Vorlesungen und Poetik-Dozenturen im literarischen Feld - Eke, Norbert Otto (Text + Kritik X/16, Sonderband: Poetik des Gegenwartsromans. Hg. von Nadine J. Schmidt und Kalina Kupczyńska)

„Um so etwas bekümmre ich mich nicht“. Grabbe und die Moral - Eke, Norbert Otto (Text + Kritik IX/16)

Der Reisende Müller - Eke, Norbert Otto (Reiseliteratur der DDR. Bestandsaufnahme und Modellanalysen)

Grabbes und Büchners Zeithorizonte - Eke, Norbert Otto (Innovation des Dramas im Vormärz: Grabbe und Büchner)

Das Politische und die Politik im Vormärz - Eke, Norbert Otto; Füllner, Bernd (Das Politische und die Politik im Vormärz)

„Aus wenigen Phonemen erstehen Welten in der Vorstellung des Zuschauers.“ Werner Fritsch: Autor, Regisseur – Visionär - Eke, Norbert Otto (Werner Fritsch: Nofretete / Das Rad des Glücks / Mutter Sprache)